2021
DOI: 10.1007/s13760-021-01720-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic capacity of hyperdense middle cerebral artery sign in anterior circulation acute ischaemic stroke patients receiving reperfusion therapy: a systematic review and meta-analysis

Abstract: Pre-intervention CT imaging-based biomarkers, such as hyperdense middle cerebral artery sign (HMCAS) may have a role in acute ischaemic stroke prognostication. However, the clinical utility of HMCAS in settings of reperfusion therapy and the level of prognostic association is still unclear. This systematic review and meta-analysis investigated the association of HMCAS sign with clinical outcomes and its prognostic capacity in acute ischaemic stroke patients treated with reperfusion therapy. Prospective and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The recruitment of immune cells following an ischemic event may be a contributing factor to this association [ 33 ]. This study used arterial spin labelling (ASL) to characterise PLH, demonstrating how advanced imaging, such as computed tomography perfusion (CTP) [ 34 , 35 ], CT angiography (CTA) [ 36 ] and ASL [ 19 ], have allowed quantitative estimation and characterisation of cerebral perfusion and the delineation of angiographic features including collateral status in AIS patients [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment of immune cells following an ischemic event may be a contributing factor to this association [ 33 ]. This study used arterial spin labelling (ASL) to characterise PLH, demonstrating how advanced imaging, such as computed tomography perfusion (CTP) [ 34 , 35 ], CT angiography (CTA) [ 36 ] and ASL [ 19 ], have allowed quantitative estimation and characterisation of cerebral perfusion and the delineation of angiographic features including collateral status in AIS patients [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modified Jadad analysis, a scoring system that analyses the methodology of a trial, was used to assess the quality of each included study [ 13 , 14 ]. The risk of funding bias was also assessed by analysing the sources of funding for each study [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies included in the meta‐analysis all obtained a score of 3. Each study was also separately assessed for risk of funding bias using a 4‐point scale that scored studies from 0 (low potential for bias) to 3 (high potential for bias) 11 …”
Section: Methodsmentioning
confidence: 99%
“…Each study was also separately assessed for risk of funding bias using a 4‐point scale that scored studies from 0 (low potential for bias) to 3 (high potential for bias). 11 The absence of industry funding was not taken to signify an absence of bias, but the presence of industry funding or conflicts of interest was assumed to be an indicator of bias. None of the included studies were found to have high potential for bias.…”
Section: Methodsmentioning
confidence: 99%
“…Reperfusion therapy, via IVT and/or EVT, is the mainstay treatment available for AIS [7,39]. Whilst the factors mediating outcomes of reperfusion therapy in AIS have been well documented [40][41][42][43][44][45][46][47], our understanding of such clinical, imaging and systems variables in the setting of IE remains sub-optimal. Current guidelines for AIS recommend the use of IVT before EVT if presentation occurs within 4.5 h of symptom onset [48].…”
Section: Reperfusion Therapy In Acute Ischaemic Stroke Patients With Infective Endocarditismentioning
confidence: 99%